2019
DOI: 10.3390/ijerph16224483
|View full text |Cite
|
Sign up to set email alerts
|

Alleviating Effect of α-Lipoic Acid and Magnesium on Cadmium-Induced Inflammatory Processes, Oxidative Stress and Bone Metabolism Disorders in Wistar Rats

Abstract: Cadmium exposure contributes to internal organ dysfunction and the development of chronic diseases. The aim of the study was to assess the alleviating effect of α-lipoic acid and/or magnesium on cadmium-induced oxidative stress and disorders in bone metabolism, kidney and liver function, and hematological and biochemical parameters changes. Male rats were exposed to cadmium (30 mg Cd/kg of feed) for three months. Some animals exposed to Cd were supplemented with magnesium (150 mg Mg/kg of feed) and/or with α-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…The elevation of serum cytokine levels in rats treated with Cd in our study is in agreement with previous reports (Bonaventura et al 2017;Markiewicz-Górka et al 2019). These results suggested that exposure to Cd stimulates the cytokines production leading to cellular immune response disorders and all of these disturbances are consequences of the oxidative damage of Cd (Bonaventura et al 2017;Turley et al 2019).…”
Section: Discussionsupporting
confidence: 94%
“…The elevation of serum cytokine levels in rats treated with Cd in our study is in agreement with previous reports (Bonaventura et al 2017;Markiewicz-Górka et al 2019). These results suggested that exposure to Cd stimulates the cytokines production leading to cellular immune response disorders and all of these disturbances are consequences of the oxidative damage of Cd (Bonaventura et al 2017;Turley et al 2019).…”
Section: Discussionsupporting
confidence: 94%
“…In addition, cadmium can disrupt the balance between bone formation and bone turnover by stimulating the differentiation and activity of osteoclasts and inhibiting the differentiation and activity of osteoblasts while inducing osteoblast-like cells to secrete a substance that stimulates the formation of bone-resorbing cells ( 33 ). Cadmium has also been linked to the overproduction of free radicals in bone and other tissues and to oxidative stress, which increases free radicals in osteoblasts and thus induces apoptosis and increased bone fragility ( 34 ). Other studies have shown that chronic exposure to cadmium also produces neurotoxic effects ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further, supplementation with ALA resulted in improved % ossification in both axial and appendicular system, and mineralization and increased the number of ossification centers in sternum, carpals, tarsals, vertebrae, pelvic bones of fetuses as compared to fetuses of dams received Ara-C alone. ALA reported to prevent bone loss induced by oxidative stress, 53 diabetes, 46,94 inflammation, 50 radiation, 54 b-adrenergic signaling, 95 periapical bone loss, 96 periodontitis, 97 fracture, 98 starvation-induced bone remodeling, 99 ovariectomy or menopausal, 49,57,100,101 high-fat diet, 58 glucocorticoids, 56,102 collagen-induced arthritis, 55,103 H 2 O 2 / Tumor Necrosis Factor-Alpha(TNF-a) 48 receptor activator of nuclear factor kappa beta (RANKL)/ TNF-a, 52 cadmium, 104 nano-zinc oxide, 105 and lead 51 and improve bone formation. Further, ALA reduces developmental anomalies in fetal skeletal system caused by diabetes.…”
Section: Discussionmentioning
confidence: 99%